2002
DOI: 10.2307/3072063
|View full text |Cite
|
Sign up to set email alerts
|

Competition for Pollination between an Invasive Species (Purple Loosestrife) and a Native Congener

Abstract: Invasive species are frequently regarded as superlative competitors that can vegetatively crowd out natives, but little is known about whether invasives can compete for pollination services with native plants. We hypothesized that, when the showy invasive species Lythrum salicaria (purple loosestrife) was present, pollinator visitation and seed set would be reduced in a native congener, L. alatum (winged loosestrife). To test this hypothesis, we constructed mixed and monospecific plots of the two species. Over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
215
4
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(229 citation statements)
references
References 41 publications
(106 reference statements)
9
215
4
1
Order By: Relevance
“…In contrast to other native-invasive plant pollinator interaction studies, where in-vasive plant species pollen is frequently found on the stigma of native plants (Brown et al 2002;Montgomery 2009aMontgomery , 2009b, almost no crown vetch pollen or any other heterospecific pollen grains were found on T. ohiensis. Morales and Traveset (2008) noted that low invasive pollen deposition on native stigmas in invaded areas could be more common than is assumed.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…In contrast to other native-invasive plant pollinator interaction studies, where in-vasive plant species pollen is frequently found on the stigma of native plants (Brown et al 2002;Montgomery 2009aMontgomery , 2009b, almost no crown vetch pollen or any other heterospecific pollen grains were found on T. ohiensis. Morales and Traveset (2008) noted that low invasive pollen deposition on native stigmas in invaded areas could be more common than is assumed.…”
Section: Discussioncontrasting
confidence: 61%
“…The great majority of these studies have determined whether or not a native species is receiving enough pollen (i.e., is pollen limited) by conducting supplemental pollinations (e.g., Powell et al 2011), or by detecting the presence of heterospecific pollen from invasive species (e.g., Brown et al 2002). Determining how good of a competitor the native species is in the absence of the invasive species is also important, as this can improve our understanding of the true impact of the invasive species.…”
Section: Introductionmentioning
confidence: 99%
“…Given that all native trees in the recipient community are wind-pollinated [70], A. altissima and R. pseudoacacia only have to face competition for pollinators by the sub-dominant undercanopy entomophilous shrubs and vines. Moreover, the latter species may facilitate exotic tree invasion by providing an established pollinator community, as found before [93], [95]. A. altissima and R. pseudoacacia also contrasted with P. alba in the year-round seed dispersal period.…”
Section: Discussionmentioning
confidence: 75%
“…This uncertainty persists despite the fact that for most flowering plants, sufficient pollen availability via animal pollination is an essential process for the long-term persistence of populations, as it directly affects seed production and genetic variability (Stanton et al 1986;Corbet 1998;Ashman et al 2004;Bell et al 2005). Few studies (except Chittka and Schürkens 2001;Brown et al 2002), however, have reported an adverse effect on native fitness resulting from competition for pollinators between invasive and native species. Few studies (except Chittka and Schürkens 2001;Brown et al 2002), however, have reported an adverse effect on native fitness resulting from competition for pollinators between invasive and native species.…”
Section: Introductionmentioning
confidence: 99%